IMPLEMENTASI KURIKULUM MERDEKA SEBAGAI STRATEGI MEWUJUDKAN SEKOLAH RAMAH ANAK DI SD MUHAMMADIYAH 14 PALEMBANG** - Muhamad Fauzi; Widya Wulandari; Airin Mey Lestari; Husnul khotimah; Daffa Aulia Padaya (STKIP Subang, 2026)
In achieving educational goals in Indonesia, it is very important to build schools as child-friendly places or environments for students. However, in reality, there are still many students who feel that school is an uncomfortable place, which of course hinders the achievement of educational goals in Indonesia. This research aims to determine the influence of the Merdeka Curriculum on learning problems at SD Muhammadiyah 14 Palembang. This research uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through interviews with teachers and students to obtain in-depth information related to the ongoing learning process. The results of this study indicate that the Merdeka Curriculum can serve as a foundation for students to feel comfortable and not feel pressured in the school environment.